2015
DOI: 10.1186/s12882-015-0208-0
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the histopathology of childhood nephrotic syndrome in Ibadan Nigeria: preponderance of idiopathic focal segmental glomerulosclerosis

Abstract: BackgroundReports on the histopathology of childhood nephrotic syndrome (NS) had emanated from our Centre since the 1960s and by the late 1980s and early 1990s, a change was observed and reported. Taking into consideration the worldwide changing trend in the histopathology of the NS and our Unit policy change in the indications for renal biopsy, a change was envisaged. We therefore evaluated the current histologic pattern of childhood NS in Ibadan with the view to highlighting any variations from the past and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 39 publications
0
36
1
Order By: Relevance
“…1960s) to membranoproliferative GN (ca. 1980s) to FSGS (present) (19). The factors responsible for the increasing incidence and prevalence of FSGS are largely unknown.…”
Section: Epidemiology and Global Burdenmentioning
confidence: 99%
“…1960s) to membranoproliferative GN (ca. 1980s) to FSGS (present) (19). The factors responsible for the increasing incidence and prevalence of FSGS are largely unknown.…”
Section: Epidemiology and Global Burdenmentioning
confidence: 99%
“…A study among children in Ibadan, in south-western Nigeria, yielded only 56 biopsies in eight years. The authors noted that renal biopsy was limited to patients who could afford it [11]. Okpechi et al reported a low rate of renal biopsies in their review of renal biopsies across Africa.…”
Section: Discussionmentioning
confidence: 99%
“…There is poor consensus on the indications for renal biopsies in children [15]. For instance, in Ibadan, there was a shift in the indication based on the trend of prevailing causes of nephrotic syndrome [11]. Nephrotic syndrome is the commonest indication for renal biopsy in most centres in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…There is a trend of increasing incidence of FSGS caused ESRD in the United States (3) and world (4).…”
Section: Introductionmentioning
confidence: 99%